Direct Contact Membrane Distillation for Desalination Brine Solution (Journal of Engineering, 2018)
Desalination is a process where fresh water produces from high salinity solutions, many ways used for this purpose and one of the most important processes is membrane distillation (MD). Direct contact membrane distillation (DCMD) can be considered as the most prominent type from MD types according to ease of design and modus operandi. This work studies the efficiency of using DCMD operation for desalination brine with different concentration (1.75, 3.5, 5 wt. % NaCl). Frame and plate cell was used with flat sheet PTFE hydrophobic type membrane. The study proves that MD is an effective process for desalination brines with feed temperature less than 60˚C especially for feed with low TDS. 37˚C, 47˚C, and 57˚C was feed temperature and 17, 22, 27˚C as permeate temperatures used in study, temperature in both sides of membrane are recorded and TDS for permeate collected to assure that there is no penetration of brine to permeate side, the results took every 30 min for time experiment of 180 min. From results, the flux increases with increasing feed temperature and flow rate, and decreasing with increasing feed concentration, experiment time, and permeate temperature.